Answer:
Answer:
The x-Intercept of is [tex]x+3[/tex] ·[tex]y=9[/tex] is [tex](9,0)[/tex]
The y-Intercept of is [tex]x+3[/tex] ·[tex]y = 9[/tex] is [tex](0,3)[/tex]
We included the graph of the function at the end of this solution.
Step-by-step explanation:
Let x + 3 · y = 9, we must transform this function into its explicit form. That is:
x + 3 · y = 9
3 · y = 9 - x
y = 3 - [tex]\frac{1}{3}[/tex] · x
Where:
x, y are the independent and dependent variables, dimensionless.
x-Intercepts correspond to such values of x such that y = 0 That is:
( y = 0)
3 - [tex]\frac{1}{3}[/tex] · x = 3
x = 9
The x-Intercept of x + 3 · y = 9 (9,0)
y-Intercepts correspond to such values of y such that x = 0. That is:
(x = 0)
y = 3
The y-Intercept of x + 3 · y = 9 is (0,3).
Finally, we proceed to graph the given function and label all intercepts.